Journal of Community Informatics Special Issue: Charting Sovereignty in the Digital Age: Tribal Leadership, Broadband, and the Rise of Tribal Digital Sovereignty: Introduction - Morris, Traci L. (The journal of community informatics, 2026)
This special issue of the Journal of Community Informatics presents a collection of articles exploring the historical trajectory and contemporary convergence of grassroots telecommunications policy advocacy in Indian Country. The articles in the special edition posit that Tribal Digital Sovereignty (TDS) has emerged as a definitive governance framework for Tribal Nations, evolving from decades of work by scholars and practitioners at the intersection of federal Indian law, telecommunications, digital equity, and tribal self-determination. The COVID-19 pandemic served as a pivotal catalyst for this evolution, recasting broadband from a luxury to an essential lifeline and exposing deep-seated disparities in connectivity. This crisis opened an unprecedented opportunity for Tribal Nations to take a seat at the policy table and invest in infrastructure through historic federal investments through the Tribal Broadband Connectivity Program and the Bipartisan Infrastructure Law. These investments have allowed Tribal governments to move beyond bridging the digital divide toward creating community-led solutions shaped by sovereignty and self-determination.Despite a shifting political and funding landscape, Tribal Nations have successfully transitioned from reactive investments to proactive self-determination in the digital realm. This special issue examines TDS as an umbrella framework encompassing both Network Sovereignty—the authority over physical infrastructure—and Data Sovereignty—the governance of information and its transmission. The articles document how Tribal governments can and are actively institutionalizing long-term strategies, including the development of regulatory codes and protocols to protect governmental and other data. By tracing historical inequities alongside recent advancements, this collection highlights a foundational shift: Tribal Nations are no longer passive beneficiaries of federal policy but are the primary architects of digital futures grounded in their unique cultural, political, and legal foundations.